The age of eclecticism : literature and culture in Britain, 1815-1885 - Bolus-Reichert, Christine, 1969- (Ohio State University Press, 2009)
"The burden of the past" invoked by any discussion of eclecticism is a familiar aspect of modernity, particularly in the history of literature. This book aims to place this dynamic in a broader context by examining the rise of a manifold eclecticism in the nineteenth century. It focuses on two understandings of eclecticism in the period--one understood as an unreflective embrace of either conflicting beliefs or divergent historical styles, the other a mode of critical engagement that ultimately could lead to a rethinking of the contrast between creation and criticism and of the very idea of the original.
Keywords: Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Criticism and interpretation.; Kingsley, Charles, -- 1819-1875 -- Criticism and interpretation.; Arnold, Matthew, -- 1822-1888 -- Criticism and interpretation.; Pater, Walter, -- 1839-1894 -- Criticism and interpretation.; Hardy, Thomas, -- 1840-1928 -- Criticism and interpretation.; Arnold, Matthew, -- 1822-1888; Hardy, Thomas, -- 1840-1928; Kingsley, Charles, -- 1819-1875; Pater, Walter, -- 1839-1894; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892; Tennyson, Alfred, -- 1809-1892.; Kingsley, Charles, -- 1819-1875.; Arnold, Matthew, -- 1822-1888.; Pater, Walter, -- 1839-1894.; Hardy, Thomas, -- 1840-1928.; Tennyson, Alfred, -- 1809-1892 -- analys och tolkning.; Kingsley, Charles, -- 1819-1875 -- analys och tolkning.; Arnold, Matthew, -- 1822-1888 -- analys och tolkning.; Pater, Walter, -- 1839-1894 -- analys och tolkning.; Hardy, Thomas, -- 1840-1928 -- analys och tolkning.; English literature -- 19th century -- History and criticism.; Eclecticism in literature.; Éclectisme dans la littérature.; Littérature anglaise -- 19e siècle -- Histoire et critique.; LITERARY CRITICISM -- General.; Eclecticism in literature; English literature; Literatur; Eklektizismus; Englisch.; 18.05 English literature.; Engelsk litteratur -- historia -- 1800-talet.; 1800-1899; Criticism, interpretation, etc.